Wind farm layout design using modified particle swarm optimization algorithm - Rehman, S. (Institute of Electrical and Electronics Engineers Inc., 2015)
Wind energy has shown tremendous potential for power generation. The energy is generated by wind turbines placed in a wind farm. To extract maximum energy from these wind farms, one of the most important issues is an efficient layout of the farms. This layout governs the location of each turbine in the wind farm. Due to its complexity, the wind farm layout design problem is classified as a complex optimization problem. Several attempts have been made previously to come up with better approaches and algorithms for optimization of wind farm. This paper proposes yet another optimization algorithm which is based on the particle swarm optimization (PSO) algorithm, which is a popular optimization algorithm. The proposed algorithm, termed as the modified particle swarm optimization algorithm (MPSO), is compared with previous results generated by another optimization algorithm, namely, genetic algorithm. Results indicate that MPSO generated better results. Â© 2015 IEEE.